Design Guidelines for Model Educational Building for Energy Conservation According to Green University - Puraprom, Wuttigarn; Kongboontiam, Punravee (Journal of Architectural/Planning Research and Studies (JARS), 2018)
There is a continuous development of green university. Policy makers are concentrating on reduction of energy usage, and the increase of efficiency in alternative energy. This study has calculated energy use of an education building by record the follow data over a 24-hour period: (1) solar radiation as source of alternative energy, (2) building materials design with low heat transfer coefficient, (3) design of outside environment to reduce air temperature difference between the inside and outside of a building. The study found solar energy can reduce 100 percent of energy used in lighting and electric. Design of building materials and the outside environment can reduce 53 percent of energy used in air-condition, which resulted in a 69 percent decrese of the overall energy use. In conclusion, the process used in this study can be effectively applied to design and renovation guidelines for a “Model educational building for energy conservation and environment”.